Dielectric Fluids for the Electrical Discharge Machining: A Review - Kunal, Kunal; Khan, Mohd. Yunus; Singh, Kishan Pal (Applied mechanics and materials, 2024)
An extensive examination of the effect of dielectric properties of the Electrical Discharge Machining (EDM) operation machining variables is being done in the present study. Irrespective of the material's hardness, an EDM is an unconventional thermo-erosion machining procedure. It gave the workpiece a better and more detailed surface topography. Dielectric is an essential EDM component that typically affects the operation's high material removal rate and surface integrity. The dielectric fluid acts as a medium that modulates electrical sparks and traps energy due to the operation. It cleans up the trash and cools the workpiece. Whenever powders like Ti, Si, graphite, Cu, Al2O3, and others are added to the dielectric fluid, the fluid's conductivity increases the micro-hardness of the substance. For executing studies in EDM, choosing a proper dielectric from the number of fluids now offered is crucial. Adopting different additives in the dielectric fluid impacts the optimization of machining parameters and related characteristics are addressed in this study in light of existing research. The studies show the effect on various output parameters.